Environmental Factors in Skin Diseases 2007
DOI: 10.1159/000106419
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors and Psoriasis1

Abstract: Psoriasis is a chronic relapsing disease characterized by variable clinical features. Several factors may exacerbate its manifestations, or even trigger the disease, such as traumatic injury to the skin, physical and psychological stress, cold weather, excessive alcohol intake, and drugs such as lithium and Beta-blockers. We describe the most common features of psoriasis and the exogenous factors that may induce, trigger or exacerbate the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 0 publications
0
27
0
2
Order By: Relevance
“…Considering the additional influence of environmental factors [78], it is tempting to argue that studies focused exclusively on genetically homogenous inbred mice, despite all their advantages, can never succeed in fully replicating human diseases and their complexity [79]. An advantage of IMQ, however, is its flexibility and convenience as an experimental approach, which in this study allowed us to demonstrate strain- and sex-dependent effects.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the additional influence of environmental factors [78], it is tempting to argue that studies focused exclusively on genetically homogenous inbred mice, despite all their advantages, can never succeed in fully replicating human diseases and their complexity [79]. An advantage of IMQ, however, is its flexibility and convenience as an experimental approach, which in this study allowed us to demonstrate strain- and sex-dependent effects.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental triggers that may precipitate or exacerbate psoriasis include endocrine factors, infections, trauma, drugs, psychological stress, obesity, smoking and alcohol consumption. 1 Alcohol intake is significantly greater in patients with psoriasis compared with normal controls, but the question is often raised: Does alcohol cause psoriasis or psoriasis cause alcoholism? A recent study showed a small but significant association between alcohol intake and anxiety and depression in patients with psoriasis, therefore it is possible that these individuals use alcohol to handle distress.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis, atopic dermatitis, rosacea and acne are all widely believed to be exacerbated by stress. Although controlled trials are difficult, there are a number of reports indicating that stress can exacerbate these conditions (Dika et al, 2007; Arndt et al, 2008; SowiƄska-Glugiewicz et al, 2005; Yosipovitch et al, 2007) and that alleviation of stress can improve some of them, such as atopic dermatitis and psoriasis (Ersser et al, 2007; Zacharieae et al, 1996). In support of this concept, there are animal models demonstrating enhancement of inflammatory skin disorders by experimental stressors (Amano et al, 2008; Pavlovic et al, 2008).…”
Section: Clinical Relevancementioning
confidence: 99%